The Helicity Sign of Flux Transfer Event Flux Ropes and Its Relationship to the Guide Field and Hall Physics in Magnetic Reconnection at the Magnetopause. Issue 11 (4th November 2022) - Dahani, S.; Kieokaew, R.; Génot, V.; Lavraud, B.; Chen, Y.; Michotte de Welle, B.; Aunai, N.; Tóth, G.; Cassak, P. A.; Fargette, N.; Fear, R. C.; Marchaudon, A.; et al.
Abstract: Flux Transfer Events (FTEs) are transient magnetic flux ropes typically found at the Earth's magnetopause on the dayside. While it is known that FTEs are generated by magnetic reconnection, it remains unclear how the details of magnetic reconnection controls their properties. A recent study showed that the helicity sign of FTEs positively correlates with the east‐west ( B y ) component of the Interplanetary Magnetic Field (IMF). With data from the Cluster and Magnetospheric Multiscale missions, we performed a statistical study of 166 quasi force‐free FTEs. We focus on their helicity sign and possible association with upstream solar wind conditions and local magnetic reconnection properties. Using both in situ data and magnetic shear modeling, we find that FTEs whose helicity sign corresponds to the IMF B y are associated with moderate magnetic shears while those that do not correspond to the IMF B y are associated with higher magnetic shears. While uncertainty in IMF propagation to the magnetopause may lead to randomness in the determination of the flux rope core field and helicity, we rather propose that for small IMF B y, which corresponds to high shear and low guide field, the Hall pattern of magnetic reconnection determines the FTE core field and helicity sign. In that context we explain how the temporal sequence of multiple X‐line formation and the reconnection rate are important in determining the flux rope helicity sign. This work highlights a fundamental connection between kinetic processes at work in magnetic reconnection and the macroscale structure of FTEs. Plain Language Summary: In the vicinity of the Earth's magnetosphere outer boundary, the magnetopause, twisted magnetic field structures known as "Flux Transfer Events" (FTEs) are often detected by spacecraft in‐situ. They temporarily connect the solar wind to the Earth's ionosphere, allowing the transfer of solar wind flux into the magnetosphere. It is known that FTEs are produced as a consequence of magnetic reconnection, a process that rearranges the topology of sheared magnetic fields, between the shocked solar wind and the geomagnetic field. However, our understanding of how the microphysics of magnetic reconnection can lead to the macroscopic structures of FTEs is still limited. We revisit the in‐situ observations of FTEs made by the Cluster and Magnetospheric Multiscale missions. We focus on the twist feature of FTEs as characterized by their helicity and investigate its relationship to solar wind conditions and possible link to magnetic reconnection properties. By investigating local magnetic shear conditions around FTE locations, we found that the FTE helicity is determined by a kinetic feature of magnetic reconnection known as the "Hall magnetic field". Our study highlights a close connection between a kinetic process of magnetic reconnection and the global structure of FTEs, constituting a cross‐scale coupling effect in solar‐terrestrial interaction. Key Points: We study the helicity sign of Flux Transfer Events and investigate upstream solar wind conditions and local magnetic shear around them The helicity sign is found to be unassociated to the Interplanetary Magnetic Field (By ) component when the local magnetic shear is high The FTEs' helicity sign in such cases may relate to the Hall field of magnetic reconnection in the absence of a guide field